Analisis Mengeringnya Likuiditas Perbankan sebagai Ancaman terhadap Denyut Perekonimian Indonesia - Ghina Jauhara; Ken William Sitompul; Likardus Kegou; Naufal Shidqi Malik; Hasyim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes the tightening of banking liquidity in Indonesia and its potential threat to national economic stability. Using a literature review approach, this research synthesizes theoretical frameworks and empirical findings related to liquidity risk, credit risk, and macroeconomic pressures affecting the banking sector. The results indicate that liquidity shortages are driven by slowing growth in third-party funds, increasing Loan to Deposit Ratio (LDR), rising Non-Performing Loans (NPL), and global financial volatility such as interest rate hikes and exchange rate fluctuations. These conditions collectively weaken banks’ capacity to meet short-term obligations and maintain intermediation functions. Liquidity risk also negatively affects banking profitability by increasing funding costs, reducing net interest margins, and limiting credit expansion. At the macro level, persistent liquidity pressures may escalate into systemic risks, trigger bank runs, reduce credit distribution to the real sector, and ultimately hamper economic performance. This study emphasizes the importance of strengthened macroprudential policies, improved liquidity management, and coordinated financial regulations to safeguard financial system stability in Indonesia.